Plasma-assisted synthesis of carbon encapsulated magnetic nanoparticles with controlled sizes correlated to smooth variation of magnetic properties. (April 2015) - Aomoa, N.; Sarmah, Trinayan; Deshpande, U.P.; Sathe, V.; Banerjee, A.; Shripathi, T.; Reddy, V.R.; Lalla, N.P.; Gupta, A.; Gupta, Rajeev; Srivastava, Divesh N.; Bordoloi, R.K.; et al.
Abstract: This paper reports rapid, continuous and carbon-nanotube free synthesis of carbon encapsulated magnetic nanoparticles by thermal-plasma expansion technique, which combines the typical advantages of high-temperature plasma assisted synthesis method with efficient particle-size control. Core nanocrystals were encapsulated with few layers of graphitized carbon, which could provide protection against both oxidation and intense chemical treatment. The average iron/iron-carbide nanoparticle diameter (7.7, 9 and 10 nm) and the width of the size distribution increased with pressure in the sample collection chamber, as a result of the decreasing quenching rate of the plasma jet. This also resulted in the smaller particles remaining frozen predominantly in the high-temperature γ-Fe phases, part of which was oxidized subsequently and eliminated preferentially during the purification process. All samples could be correlated with smooth variation of magnetic properties; saturation magnetization, remnant magnetization and coercive-field enhancing with increasing chamber pressure or average particle size. The low pressure synthesized sample with smallest average particle size approached super-paramagnetic behavior (saturation magnetization = 51.8 emu/g, ratio of remnant to saturation magnetization = 4.9 and coercive field = 52 Oe), which may be ideal for biomedical applications. High-pressure samples on the other hand have a higher saturation magnetization (76.3 emu/g) and coercive fields (123 Oe).